CURRENT ISSUES OF ENERGY EFFICIENCY IMPROVEMENT IN MODERN ECONOMIC CONDITIONS - Berdnikova, I.; Kiseleva, E.; Baeva, D.; Solovyeva, I. (Scientific Journal of Pedagogy and Economics, 2020)
Electricity consumption is constantly growing in the world. In this connection, there are new urgent problems of increasing energy efficiency and energy conservation. Exactly, the economic development of countries and the change in the citizens’ life quality depends on successful solutions in this sphere. In addition, energy efficiency today is the most important developmental indicator of the national economy. The article discusses electricity consumption statistics in the world, a comparative analysis of the statutory conditions and the main implementing energy efficiency methods and programs in different countries.